Assessment of Glenohumeral Internal Rotation Deficit and Scapula Upward Rotation Differency Within Hungarian NB2Handball Players - Máté PINTÉR; Iuliana BOROS-BALINT; Márta HOCK; Melinda JÁROMI; Alexandra MAKAI; Eleonóra LEIDECKER (Cluj University Press, 2024)
The aim of our cross-sectional study was to assess the rotational range of motion of the shoulder joint and the scapula movement of Hungarian NBII handball players, to find out how many athletes may be affected by a rotational range of motion deficit. We also wanted to gain insight into whether players with GIRD report more pain. The study was conducted between September and October 2023. We studied 31 male handball players, all of whom participated in training sessions at least 3 times a week. The survey showed that more than half of the athletes were affected by some level of range of motion deficit. Of those assessed, 29% were affected by Glenohumeral Internal Rotation Deficit (GIRD) and 55% by Total Arc of Motion Deficit (TAMD). Those who had at least 15° of internal rotation deficit during pretesting had significantly less scapula upward rotation in the neutral shoulder, 60° abduction and 90° abduction positions. No significant difference was found in the 120° shoulder abduction position. For the non-dominant upper limb, no significant difference was found between the two groups. Athletes with GIRD reported significantly greater pain on the VAS scale than those without internal rotation deficit.